Nilai-Nilai Pendidikan Islam dalam Kesenian Wayang - Andini; Ichsan, Yazida; Triyana, Fita; Fitri, Khalidah (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2021)
Wayang Kulit is a very important art to be preserved considering the many values of life that exist in Wayang Kulit itself. The values of Islamic education can also be found in Wayang Kulit art. This study aims to determine that values of Islamic education in the art of Wayang Kulit and the role of the younger generation in preserving the Wayang Kulit. The research of Islamic education values within Wayang Kulit is conducted based on library research. Essentially, the Wayang Kulit is still exist until today, but the problem relied on it is the fact that young generation has not been built to preserve this art. Besides, the Islamic of Indonesian values can be found within the soul of Wayang Kulit, such as in the epic story of Ramayana dan Mahabharata. Wayang Kulit is not merely an art to entertain people, but its role can also be taken as one of educational method. It because within the story of Wayang Kulit itself relied some great, moral, and ethics values.